Synovial sarcoma mimicking a thoracic dumbell schwannoma- a case report*. (2nd January 2020) - Subramanian, Susanth; Jonathan, Gandham Edmond; Patel, Bimal; Prabhu, Krishna
Abstract: Introduction: Synovial sarcoma is a rare mesenchymal malignant neoplasm that accounts for less than 10% of soft tissue sarcomas. About 95% of the sarcomas occur in the extremities. Primary synovial sarcomas of the spine are a rare tumor arising from the paravertebral regions, paraspinal muscles or epidural spaces. Purpose: To report an atypical radiological presentation of synovial sarcoma of the thoracic spine mimicking a nerve sheath tumor in an elderly adult and describe the management with review of the literature. Clinical presentation: A forty-six-year-old lady presented with clinical features of a thoracic intradural extramedullary cord compression at T7 level. She was Nurick grade 4 at presentation. MRI of the Thoracic spine with whole spine screening showed a contrast enhancing intradural extramedullary tumor at the T7-8 level; the tumor was exiting out through the left T7-8 neural foramina with foraminal widening. The possibility of a schwannoma was considered. Intervention: She underwent a T7-8 laminectomy and total excision of the tumor followed by posterior fusion. The biopsy was reported as synovial sarcoma. She subsequently underwent radiation and chemotherapy. She had marked improvement in her Neurological status and remained disease free at six months follow-up. Conclusion: Synovial sarcoma of the spine is a rare mesenchymal malignant neoplasm. One needs to consider Synovial sarcoma as one of the differential diagnosis of intradural tumors of the spine.